Subcutaneous C.E.R.A. for the Treatment of Chronic Renal Anemia in Predialysis Patients - Sedat Üstündağ; Ekrem Doğan; Murat Duranay; Rümeyza Kazancıoğlu; Vedat Çelik; Abdülkadir Ünsal; Lütfullah Altıntepe; Belda Dursun; Ertuğrul Akbaş; Alaattin Yıldız (Balkan Medical Journal, 2016)
Background: We investigated the efficacy, safety and tolerability of once-monthly administration of C.E.R.A. in erythropoiesis stimulating agents (ESAs) naive predialysis patients with CKD for anemia treatment